2020
DOI: 10.1055/s-0040-1721294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Panoramic Radiographs in Relation to the Mandibular Third Molar and to Incidental Findings in an Adult Population

Abstract: Objectives The aim was to evaluate the characteristics of the mandibular third molars, especially in relation to the inferior alveolar nerve. Further aims were to investigate incidental findings in panoramic radiographs in an adult population, and to investigate image quality related to patient positioning. Materials and Methods From a previous study with 451 randomly selected adult participants who lived in Sweden, 442 panoramic radiographs from four dental public health clinics were used. The third molars’ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
11
2
Order By: Relevance
“…Lower prevalence of 0.4% [ 21 , 23 ], 0.5% [ 24 ], 1.86% [ 2 ], 2% [ 13 ], and 2.9% [ 25 ] for periapical inflammatory lesions have been found. Other studies have reported higher prevalence of periapical inflammatory lesions ranging from 25–28.6% [ 18 , 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lower prevalence of 0.4% [ 21 , 23 ], 0.5% [ 24 ], 1.86% [ 2 ], 2% [ 13 ], and 2.9% [ 25 ] for periapical inflammatory lesions have been found. Other studies have reported higher prevalence of periapical inflammatory lesions ranging from 25–28.6% [ 18 , 19 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most (86%) of the respondents (response options: always or often ) would use panoramic radiographs in pre-surgical assessment of the mandibular third molars if possible. This is expected since the panoramic unit is commonly accessible, the image provides a useable overview, and in many cases, it is sufficient for a pre-surgical examination of the third molar [ 2 ]. Also, it is a cost-effective choice [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…A panoramic radiograph has lower spatial resolution and is thus less detailed than intraoral radiographs; however, it provides a useable overview of the teeth, bone, and anatomical structures in the maxillofacial area and is considered a useful method for many third molar cases before surgical removal [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, CBCT imaging delivers a higher radiation dose compared with panoramic radiographs. 11,12 In this study, we developed a computer-aided diagnosis (CAD) system to assist osteoporosis assessment based not only on MCW but also on analysis of the texture of the cortical bone representing the bone porosity. This assessment was performed using digital panoramic radiographs and patients were classified into normal, osteopenia, or osteoporosis groups using multiclass classification with the support vector machine (SVM).…”
Section: Introductionmentioning
confidence: 99%